Characteristics and Differences in Mpox Patients with and without HIV Infection: A Retrospective Cross-Sectional Study in Chengdu, China - Zhao B; Liu Q; Du Q; Kang J; Tang R; Tu Y; Liu D (International Journal of General Medicine, 2024)
Bennan Zhao,1,* Qingxiao Liu,2,* Qing Du,3 Jun Kang,1 Rong Tang,4 Yalan Tu,5 Dafeng Liu1 1The First Ward of Internal Medicine, Public Health Clinical Center of Chengdu, Chengdu, People’s Republic of China; 2Department of Neurology, Hospital of Chengdu University of TCM, Chengdu, People’s Republic of China; 3The Second Ward of ICU, Public Health Clinical Center of Chengdu, Chengdu, People’s Republic of China; 4Department of Integrated Chinese and Western Medicine, Public Health Clinical Center of Chengdu, Chengdu, People’s Republic of China; 5Scientific Research and Teaching Department, Public Health Clinical Center of Chengdu, Chengdu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Dafeng Liu, The First Ward of Internal Medicine, Public Health Clinical Center of Chengdu, Chengdu, People’s Republic of China, Tel +86 1 309 449 4836, Email ldf312@126.com Yalan Tu, Scientific Research and Teaching Department, Public Health Clinical Center of Chengdu, Chengdu, People’s Republic of China, Tel +86 1 501 326 6454, Email tyl950330@163.comPurpose: To date, there are few reports about mpox case series in China, and scarce information is available about the in-vivo kinetics of T-cell responses in the early stage of mpox infection. This study aims to investigate the clinical difference among mpox patients with and without human immunodeficiency virus (HIV) infection.Patients and Methods: A total of 56 patients diagnosed with mpox by Chengdu Center for Disease Control and Prevention (CDC) and hospitalized in Public Health Clinical Center of Chengdu were retrospectively included and divided into an HIV-infected group (n=23) and a non-HIV-infected group (n=33). Clinical characteristics and serum chemistry findings of mpox patients were collected in order to analyze the differences between the HIV-infected group and the non-HIV-infected group.Results: Multiple laboratory abnormalities, including elevated C-reactive protein (69.1%), hypocalcemia (50.9%), elevated CD3+CD8+T counts (47.0%) and inverted ratio of CD3+CD4+T to CD3+CD8+T (64.7%) were common in mpox cases. There were statistically significant differences (all P < 0.05) in age, serum calcium levels, CD3+CD4+T counts, the ratio of CD3+CD4+T to CD3+CD8+T, proportion with > 10 rashes, incidence of proctitis anus and time from rash growth to rash scab shedding between HIV-infected group and non-HIV-infected group. In the early stage of mpox infection, the median of CD3+CD8+T counts in the non-HIV-infected group was significantly higher than that in healthy donors (P< 0.001), and the median of CD3+CD4+T/CD3+CD8+T ratio was significantly lower (P< 0.001). The median of CD3+CD4+T counts in mpox patients co-infected with HIV significantly decreased compared to the pre-infection level (p =0.033).Conclusion: Our study indicates that mpox co-infected with HIV patients have longer lasting rash lesions and a higher incidence of proctitis anus. T-cell responses may be different between HIV-infected and non-HIV-infected individuals in the early stage of mpox infection.Keywords: mpox, HIV, clinical characteristics, complication, T-cell response